Providing evidence from practice: Evaluating 4.5 years of implementing diabetes education support program in carbohydrate management - Mergelsberg, Enrique L.P.; Olson, Jenny L.; Moore, Sheryl; Jensen, Jessica F.; Seivwright, Hayley; Norman, Richard; Watson, Natasha A. (Patient education and counseling, 2022)
To evaluate personal and economical outcomes of CarbSmart, a 3-hour person-centered, theory-based program implemented throughout Australia, targeting optimal dietary carbohydrate management. More than 500 CarbSmart programs were implemented over 4.5 years. Pre-, post-, (N = 4656) and 3-month follow-up assessments (N = 188) of knowledge, empowerment, confidence, and patient activation were collected from people with diabetes. Participant satisfaction and potential annual cost-savings were calculated. Repeated measures ANCOVAs showed large improvements pre- to post-program in all outcome variables (d = 0.80–1.68), which were maintained at 3-month follow-up in a sub-sample. Participant satisfaction was high (Net Promoter Score = 72.3). Potential annual cost-savings nation-wide were estimated at US$512million. This paper provides evidence that CarbSmart is effective in improving behavioral indicators of self-management outcomes in Australians living with diabetes. CarbSmart has the potential to prevent diabetes-related complications. However, not engaging people living with diabetes with lower levels of patient activation at baseline was recognized as a future opportunity to improve the impact of our service. Strategies are needed to engage people with lower activation levels to improve outcomes in vulnerable and at-risk populations. The development of CarbSmart was funded by Diabetes WA, the national implementation of CarbSmart by the National Diabetes Services Scheme, an initiative of the Australian Government. •Routine evaluation of 4656 people with diabetes across 550 program implementations.•Significant increases in confidence and knowledge in carbohydrate self-management.•Significant increase in patient activation and diabetes empowerment.•Maintained changes at 3-month follow-up in all outcomes.•Estimated annual cost-savings were approximately US$512million.